Connecting Jesus to social justice : classical christology and public theology - Hughson, D. Thomas (Lanham, MD : Rowman & Littlefield Publishers, Inc., 2013)
Connecting Jesus to Social Justice argues a doctrinally traditional, orthodox basis for Christian participation in the public sphere on behalf of social justice. The book addresses a situation internal to churches in the U.S. from a Catholic perspective yet not without analogies in other churches and Christian movements. This book is a contributive, as well as distributive, idea of social justice from Catholic social teaching. The chapters take into account discussion on the public sphere and propose a theologically-principled, ecumenical and interreligious public for social justice.
Public theology : some elements -- An illustrative problem -- Is it really a problem? : Benedict XVI and social justice -- Christological solution : divine and human natures -- Christological solution : one divine person -- Public theology : interior, ecumenical, interreligious -- Epilogue : Jesus and social justice.
Includes bibliographical references (pages 281-295) and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Social justice -- Religious aspects -- Catholic Church; Theology, Practical; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Social justice -- Religious aspects -- Catholic Church; Electronic books